Common Fixed Points of Two Mappings regarding a Generalized c-Distance over a Banach Algebra. (11th March 2021) - Aryanpour, Ladan; Rahimi, Hamidreza; Soleimani Rad, Ghasem
Abstract : In this article, applying the concept of a generalized c -distance in cone b -metric spaces over Banach algebra with a nonnormal solid cone therein, we establish several common fixed point theorems for two noncontinuous mappings satisfying the Han-Xu-type contraction. Our results are interesting, since they are not equivalent to former well-known results regarding a w t -distance in b -metric spaces while they contain recent results corresponding to a generalized c -distance in cone b -metric spaces.